The role of reaction temperature in synthesizing clove-derived copper oxide nanoparticles for brain cancer treatment - Mehrnoosh Fakhredin; Fatemeh Shariatmadar Tehrani; Maryam Aliannezhadi (Results in Physics)
The study investigates the effects of reaction temperature (25°C, 50°C, and 80°C) and calcination on copper oxide nanoparticles (CuO NPs) synthesized by the bio-sol–gel method using clove extract. The results demonstrate the significant impact of reaction temperature on the properties of both as-synthesized and calcined nanoparticles produced by the bio-sol–gel method. The results show that reaction temperature significantly controls the crystalline properties of the as-synthesized samples, however, it is not a significant factor in the crystalline nature of the calcined samples. The increase in reaction temperature enhances the crystallite size for both as-synthesized and calcined nanoparticles. Additionally, it is verified that the calcination process influenced the structural, morphological, and optical properties of the synthesized nanoparticles, yielding narrow-band gap CuO NPs in monoclinic crystalline structure in all reaction temperatures. Notably, CuO NPs obtained at a reaction temperature of 50°C exhibited better primary properties, facilitating their potential application in cancer treatment. Brain tumors constitute a disproportionately significant contributor to the overall cancer mortality burden, particularly in cases where surgical intervention is not a viable treatment option. Therefore, the efficacy of the selected bio-synthesized CuO NPs is systematically assessed within the context of cancer treatment, with a particular emphasis on their effects on the C6 brain tumor cell line. The CuO NPs displayed remarkable anti-cancer activity against the C6 cell line, with increased drug concentrations in the wells resulting in high cytotoxicity. Significant cytotoxic effects were observed with the selected CuO NPs at a concentration of 35 µ g/mL.